Rapid disintegrating tablets of simvastatin dispersions in polyoxyethylene–polypropylene block copolymer for maximized disintegration and dissolution - Balata GF; Zidan AS; Abourehab MA; Essa EA (Dove Medical Press, 2016)
Gehan F Balata,1,2 Ahmad S Zidan,2 Mohamad AS Abourehab,1,3 Ebtessam A Essa4 1Department of Pharmaceutics, Faculty of Pharmacy, Umm Al-Qura University, Makkah, Saudi Arabia; 2Department of Pharmaceutics, Faculty of Pharmacy, Zagazig University, Zagazig, 3Department of Pharmaceutics, Faculty of Pharmacy, El-Minia University, El-Minia, 4Department of Pharmaceutics, Faculty of Pharmacy, Tanta University, Tanta, Egypt Abstract: The objective of this research was to improve the dissolution of simvastatin and to incorporate it in rapid disintegrating tablets (RDTs) with an optimized disintegration and dissolution characteristics. Polyoxyethylene–polypropylene block copolymer (poloxamer 188) was employed as a hydrophilic carrier to prepare simvastatin solid dispersions (SDs). Fourier transform infrared spectroscopy, differential scanning calorimetry (DSC) and X-ray diffractometry were employed to understand the interaction between the drug and the carrier in the solid state. The results obtained from Fourier transform infrared spectroscopy showed absence of any chemical interaction between the drug and poloxamer. The results of differential scanning calorimetry and X-ray diffractometry confirmed the conversion of simvastatin to distorted crystalline state. The SD of 1:2 w/w drug to carrier ratio showed the highest dissolution; hence, it was incorporated in RDT formulations using a 32 full factorial design and response surface methodology. The initial assessments of RDTs demonstrated an acceptable flow, hardness, and friability to indicate good mechanical strength. The interaction and Pareto charts indicated that percentage of croscarmellose sodium incorporated was the most important factor affecting the disintegration time and dissolution parameter followed by the hardness value and their interaction effect. Compression force showed a superior influence to increase RDT’s porosity and to fasten disintegration rather than swelling action by croscarmellose sodium. On the other hand, croscarmellose sodium was most important for the initial simvastatin release. The results suggest the potential use of poloxamer 188-based SD in RDT for the oral delivery of poor water-soluble antihyperlipidemic drug, simvastatin. Keywords: simvastatin, poloxamer 188, croscarmellose sodium, full factorial design, dissolution